The effect of FeUP (Fe uptake package) box on adherence to iron tablet intake among adolescent girls with anemia - Dinda Puput Purwanti; Linda Amalia; Afianti Sulastri (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Anemia remains a major health problem among adolescent girls. Although the distribution of iron tablets continues to expand, adherence remains low due to forgetfulness, lack of motivation, and insufficient monitoring. The FeUP (Fe uptake package) Box is an integrated adherence support intervention that combines a pill box, educational and instruction cards, a self monitoring card, and parental involvement to simultaneously address these barriers and improve adherence to iron tablet intake. Purpose: To analyze the effectiveness of the FeUP box in improving adherence to iron tablet intake among adolescent girls with anemia. Method: A quasi-experimental study was conducted using a nonequivalent control group with a pretest–posttest design. Participants were selected through purposive sampling from SMPN 29 Bandung, within the Ledeng Community Health Center service area, and SMPN 2 Parongpong, within the Ciwaruga Community Health Center service area. The sample consisted of 52 adolescent girls diagnosed with anemia, divided equally into an intervention group (n = 26) and a control group (n = 26). Adherence to iron tablet consumption was assessed using the Morisky Medication Adherence Scale-8 (MMAS-8). The intervention group received FeUP Box educational materials for four weeks, while the control group followed the school’s standard iron supplementation program without additional education. Data analysis employed the Wilcoxon Signed-Rank Test to examine within-group changes in adherence and the Mann-Whitney U Test to compare adherence outcomes between the intervention and control groups. Results: Adherence scores in the intervention group increased from 3.57 ± 1.37 (95% CI: 3.01–4.12) to 5.25 ± 1.23 (95% CI: 4.75–5.75) after the intervention, with a significant improvement (p < 0.001; r = 0.692). In contrast, no significant change was observed in the control group, with adherence scores changing from 3.04 ± 1.46 (95% CI: 2.45–3.63) to 2.86 ± 1.33 (95% CI: 2.32–3.39) (p = 0.317; r = 0.196). The increase in adherence scores was significantly greater in the intervention group than in the control group (p < 0.001; r = 0.585). As a supporting objective measure, hemoglobin levels in the intervention group showed an upward trend after the intervention; however, the increase was not statistically significant. Conclusion: The FeUP box effectively improved adherence to iron tablet intake among adolescent girls with anemia. Integrating the FeUP box into school-based iron supplementation programs may provide a practical strategy to strengthen adherence and support anemia prevention among adolescent girls.